2021
DOI: 10.3390/toxins13110787
|View full text |Cite
|
Sign up to set email alerts
|

Human Proximal Tubule Epithelial Cells (HK-2) as a Sensitive In Vitro System for Ochratoxin A Induced Oxidative Stress

Abstract: Ochratoxin A (OTA) is a mycotoxin that is potentially carcinogenic to humans. Although its mechanism remains unclear, oxidative stress has been recognized as a plausible cause for the potent renal carcinogenicity observed in experimental animals. The effect of OTA on oxidative stress parameters in two cell lines of LLC-PK1 and HK-2 derived from the kidneys of pig and human, respectively, were investigated and compared. We found that the cytotoxicity of OTA on LLC-PK1 and HK-2 cells was dose- and time-dependent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 84 publications
1
4
0
Order By: Relevance
“…Oxidative stress in cells is often accompanied by abnormal accumulation of ROS [25]. Abnormally increased ROS can have various toxic effects on tubule epithelial cells and even cause autophagy and apoptosis [26,27]. In the current work, we first verified the oxidative stress of TAC on normal kidney cells and found that TAC markedly induced oxidative stress and apoptotic cell death in HK-2 cells, which was in line with the observations of previous studies [28][29][30].…”
Section: Discussionsupporting
confidence: 89%
“…Oxidative stress in cells is often accompanied by abnormal accumulation of ROS [25]. Abnormally increased ROS can have various toxic effects on tubule epithelial cells and even cause autophagy and apoptosis [26,27]. In the current work, we first verified the oxidative stress of TAC on normal kidney cells and found that TAC markedly induced oxidative stress and apoptotic cell death in HK-2 cells, which was in line with the observations of previous studies [28][29][30].…”
Section: Discussionsupporting
confidence: 89%
“…It is likely that the reduced expression of these genes results in decreased antioxidant defense and in turn increased oxidative stress and macromolecular damage. In contrast, several reports suggest that antioxidant enzymes such as SOD1, HO1, GPX1, and G6PD can be activated through increased ROS levels and the increased expression of Nrf2 [ 51 , 52 , 56 , 57 ]. Nonetheless, it is clear that OTA induces oxidative stress in the kidney and liver: directly via redox cycling and indirectly via reducing cellular defense involving antioxidants.…”
Section: Ochratoxin a (Ota)mentioning
confidence: 99%
“…The treatment of a pig kidney cell line (LLC-PK1) with increasing concentrations of OTA decreased SOD activity and increased the intracellular levels of ROS in a dose-dependent manner [42]. In a recent study, Garcia et al found the downregulation of glucose-6-phosphate dehydrogenase (G6PD) and GPx mRNA levels in LLC-PK1, whereas CAT and SOD were upregulated in human kidney cells (HK-2) after being exposed to OTA [17]. An in vivo toxicity study on the relationship between OTA and oxidative stress in rats showed an increase in MDA levels in the kidney as well as the downregulation of GPx and SOD gene expression [44].…”
Section: Ota Mechanisms Of Kidney Toxification: Focus On Oxidative St...mentioning
confidence: 99%
“…According to animal studies in murine models, OTA-induced renal toxicity and genotoxic effects are most likely mediated by the formation of free radicals, which can lead to kidney cancers (EFSA, 2006). The generation of reactive oxygen species (ROS) is one of the key cellular processes that cause OTA-induced kidney damage, even if the molecular mechanisms behind its effects are unknown as of yet [17].…”
Section: Introductionmentioning
confidence: 99%